2018
DOI: 10.3389/fimmu.2018.02072
|View full text |Cite
|
Sign up to set email alerts
|

TFPI-2 Protects Against Gram-Negative Bacterial Infection

Abstract: Tissue factor pathway inhibitor-2 (TFPI-2) has previously been characterized as an endogenous anticoagulant. TFPI-2 is expressed in the vast majority of cells, mainly secreted into the extracellular matrix. Recently we reported that EDC34, a C-terminal peptide derived from TFPI-2, exerts a broad antimicrobial activity. In the present study, we describe a previously unknown antimicrobial mode of action for the human TFPI-2 C-terminal peptide EDC34, mediated via binding to immunoglobulins of the classes IgG, IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…LCN2 could be a useful factor in the study of canine trophoblast invasiveness and may be an indicator of activity during gestation. TFPI2, called also as a matrix-associated serine protease inhibitor, has been found in human placentas, especially in the vascular endothelial cells and the microvilli of placental syncytiotrophoblasts [1,25,40]. The function of TFPI2 is proposed to promote trophoblast invasion by relating to MMP-2 and MMP-9 expressions [46].…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 could be a useful factor in the study of canine trophoblast invasiveness and may be an indicator of activity during gestation. TFPI2, called also as a matrix-associated serine protease inhibitor, has been found in human placentas, especially in the vascular endothelial cells and the microvilli of placental syncytiotrophoblasts [1,25,40]. The function of TFPI2 is proposed to promote trophoblast invasion by relating to MMP-2 and MMP-9 expressions [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although TFPI-1 accounts for only about 30% of the total TFPI in plasma, it is considered the more potent anticoagulant form 42 . TFPI-2 might rather be relevant for host defense than for anticoagulant functions 43 . Interestingly, a releasable pool of TFPI-1 seems to derive not directly from endothelial cells but from the extravascular space 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in TFPI conditional knockout mice, TFPI deficiency worsened sepsis-induced ALI/ARDS and reduced survival rates [98]. Several reports have demonstrated that TFPI can be used in the treatment of Gram-negative bacterial infections, suggesting a therapeutic strategy targeting the coagulation pathway [100][101][102], and nebulized or injected recombinant human TFPI has been reported to mitigate both pulmonary and systemic coagulation [103,104]. However, the relationship between the efficacy of exogenous TFPI and the dosage, as well as any associated side effects, remains to be explored.…”
Section: Coagulant Damagementioning
confidence: 99%